Pengaruh Kompetensi, Independensi dan Due Professional Care Terhadap Kualitas Internal Audit Pada PT. OTO Multiartha Jakarta - Patriandari -; Peri Heryanto (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2019)
This study discusses the effect of competence, independence and due professional care to the quality of internal audit. The independent variables are competence, independence, and due professional care as well as the dependent variable is the quality of the audit was measured using a Likert scale consisting of five proxy votes. The population in this study is an internal audit on PT. Oto Multiartha in Jakarta 2015. The research sample was determined by the method of non probablity with the kind of purposive sampling. Sample of 34 respondents to the consideration of the existing internal auditor only PT.Oto Multiartha office at the time of the questionnaire were distributed. Data were analyzed using multiple regression analysis. Based on research, it can be concluded that simultaneous variable competence, independence, and due professional care, which is measured using a Likert scale have an impact on audit quality, this is indicated by the value of Fcount is greater than the value Ftable is 18.606> 2.920 as well as significant values ​​(sig t ) less than 0.05 is 0.000 <0.05, while partially concluded that competence variable (X1) effect on the quality of internal audit (Y), this is indicated by tcount greater than the value ttable is 3.130> 2.042 as well as significant values (sig t) less than 0.05 is 0.004 <0.05. Variable independence (X2) effect on the quality of internal audit (Y), this is indicated by tcount greater than the value ttable is 7.298> 2.042 as well as significant values ​​(sig t) less than 0.05 is 0.000 <0.05. While variable due professional care (X3) has no effect on the quality of internal audit (Y) with significant values ​​(sig t) over 0.05 is 0.138> 0.05